National Education Policy 2020 and Sustainable Development Goals: A Roadmap for Education Reform in India - Parveen, Shakera (AG Volumes, 2025)
A vital human right, education gives individuals the information and skills they need to enhance their health and well-being, expand their work opportunities, and combat poverty. Education policy is the means by which high-quality education, the cornerstone and foundation of every society’s growth, may be achieved. Research the papers that discuss the Sustainable Development Goals and the national education strategy for 2020. Based on a study of the literature, it was determined that NEP 2020, which aligns with the 2030 Goals for Sustainable Development, aims to establish India as a global knowledge centre by promoting technology-driven, flexible, and interdisciplinary education. SDG 4 provides a universal blueprint that guides education policies to prioritize foundational literacy, inclusivity, and digital learning. Higher education institutions are essential to this shift because they include sustainability ideas into their courses, giving students the abilities, information, and moral perspective they need to tackle global issues. Furthermore, teacher training programs must be strengthened to incorporate SDGs into education, ensuring that educators are well-prepared to impart sustainability-driven learning.